Køn og genre i TAXA: Følsom maskulinitet og mødre under anklage - Pedersen, Vibeke (Kvinder, Køn & Forskning, 1998)
The article looks at the new Danish prime-time soap opera "Taxa", asking why a usually devaluated women’s genre as the soap opera has succeeded in addressing the entire family in prime time on Sunday evening. The serial is discussed in the light of Christine Gledhill’s statement that in the new prime-time soap "melodrama and realism, women’s and men’s culture, intersect (...) in a particularly productive way". I conclude that while it is true that the male characters in "Taxa" are multi-dimensional personalities, women in this Danish soap opera are not only almost absent as writers and directors, but the female figures are also highly mythologized. Thus the costs of the soap genre going mainstream are marginalization and trivilization of women.